A study on initiation of breastfeeding: are children in India getting the best start? - Kushwaha, Arvind Singh; Kushwaha, Anshika; Kushwaha, Neha (International Journal Of Community Medicine And Public Health, 2018)
Background: Giving colostrum to a newborn has been called the “first immunisation” of the child. Colostrum and breast milk have definite anti-infective properties and have shown to have an impact on reducing specific morbidity and mortality rates among infants. The objectives of the study were to determine the level of knowledge about early initiation of breast feeding amongst mothers and to study determinants of initiation of breast feeding. Methods: Cross-sectional analytical study was carried out at a tertiary care hospital of a medical college in Pune. Systematic random sampling method was used. Results: The subjects came predominantly from joint families, urban area, Hindu by religion and Class II Socio economic status (Kuppuswamy classification). Majority of (84.23%) mothers responded that they initiated breast feeding within 1 hour after birth. Most (95.25%) of the mothers agreed for giving colostrums. About half of the mothers interviewed believed that breast milk is more nutritious (49.5%) while 28% mothers said that feeding babies with breast milk protects them against infections. Conclusions: All doctors and paramedical personnel in the Government and private institutions ensure that lactation begins immediately after birth and prelacteal feeds are withheld.